2021
DOI: 10.26508/lsa.202101046
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase backtracking results in the accumulation of fission yeast condensin at active genes

Abstract: The mechanisms leading to the accumulation of the SMC complexes condensins around specific transcription units remain unclear. Observations made in bacteria suggested that RNA polymerases (RNAPs) constitute an obstacle to SMC translocation, particularly when RNAP and SMC travel in opposite directions. Here we show in fission yeast that gene termini harbour intrinsic condensin-accumulating features whatever the orientation of transcription, which we attribute to the frequent backtracking of RNAP at gene ends. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 70 publications
(126 reference statements)
6
9
0
Order By: Relevance
“…Release of this pause on full transcription in DP cells re-widens the TAD boundary again, which could be explained if the polymerase acted as a mobile loop extrusion barrier. Similar gene body-broadened boundaries have recently been reported on metagene analysis in a parallel study (Banigan et al, 2022), and we have recently proposed in fission yeast that paused or backtracking RNA polymerase may have different effects on condensin-mediated loop extrusion to elongating polymerase (Rivosecchi et al, 2021). Ectopic induction of the gene had no effect on local chromatin topology in ESCs, but the boundary was already rather wide, so the model is not necessarily disproved.…”
Section: Discussionsupporting
confidence: 77%
“…Release of this pause on full transcription in DP cells re-widens the TAD boundary again, which could be explained if the polymerase acted as a mobile loop extrusion barrier. Similar gene body-broadened boundaries have recently been reported on metagene analysis in a parallel study (Banigan et al, 2022), and we have recently proposed in fission yeast that paused or backtracking RNA polymerase may have different effects on condensin-mediated loop extrusion to elongating polymerase (Rivosecchi et al, 2021). Ectopic induction of the gene had no effect on local chromatin topology in ESCs, but the boundary was already rather wide, so the model is not necessarily disproved.…”
Section: Discussionsupporting
confidence: 77%
“…We considered that RNAPII accumulated in the intergenic region of the convergent genes could be a trace of RNAPII backtracking activity and a recent study also reported that backtracking of RNA polymerase induces the accumulation of condensin (Rivosecchi et al, 2021). Consistent with a previous study in mammalian cells (Busslinger et al, 2017), at symmetrically expressed sites, Rad21 was positioned symmetrically, and this correlated with the accumulated Ser2P signals at the same converging intergenic sites.…”
Section: Nuclear Exosome and Pfs2 Regulate The Higher-order 3d Genome Architecture Via Rad21supporting
confidence: 79%
“…Recently, a study in fission yeast reported that the RNA polymerase backtracking at gene termini might contribute to the accumulation of condensin, another SMC complex (Rivosecchi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Given the presence of condensin-dependent TADs at subtelomeres, it is tempting to speculate that condensin-mediated loop extrusion ( 2, 3 ) provides the power stroke to disentangle telomeres, even when Top2 is impaired thanks to the proximity of DNA ends. By analogy with the enrichment of condensin at highly expressed genes ( 22, 23 ), Taz1 bound to telomeres might create an obstacle onto which loop-extruding condensin complexes accumulate in metaphase (Fig. 4D).…”
Section: Figmentioning
confidence: 99%